Unusual Cardiac Presentation of COVID-19 and Use of Convalescent Plasma. (6th October 2020) - Hartman, William R.; Hess, Aaron S.; Connor, Joseph P.
Abstract : COVID-19 infection caused by the SARS-CoV-2 virus has been associated with cardiac abnormalities, including conduction abnormalities. Convalescent plasma is emerging as a potentially safe and effective treatment option for patients severely or critically ill with COVID-19. Here, we describe a case of a COVID-19 patient with new-onset cardiac ectopy who had near resolution of his cardiac sequelae following convalescent plasma transfusion.